THE EFFECT OF REWARD, PUNISHMENT, WORK ENVIRONMENT, INCENTIVES, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE BATU AJI SUB-DISTRICT OFFICE, BATAM CITY - Martini Plantika Dwi Utama; Sri Langgeng Ratnasari; Ervin Nora Susanti (RADJA PUBLIKA, 2026)
The purpose of this study was to see how rewards, punishments, work environment, incentives, and work discipline impact employee performance at the Batu Aji District Office in Batam City. Employee performance plays an important role in the success of a company, so it is important to understand the components that influence it. This study was conducted quantitatively, and a survey was conducted on fifty employees. The data was analyzed using multiple linear regression after being collected through a questionnaire. The results showed that rewards, punishments, work environment, incentives, and work discipline were significantly correlated with employee performance. While punishment did not have a significant impact on employee performance, rewards, work environment, incentives, and work discipline were proven to have the greatest partial influence on their performance. The results can be used as a recommendation for management to pay more attention to these aspects to improve employee performance at the Batu Aji Sub-District Office.